Sustainable water management through green economy? - Annabelle Houdret; Elke Herrfahrdt-Pähle; Waltina Scheumann; Ines Dombrowsky (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
Twenty years after the international community meeting in Rio de Janeiro agreed on the triad of ecological, economic and social sustainability, the subject of the green economy is gaining ground in debates on the environment and development. Many international organisations have developed their own definitions and programmes designed to boost economic growth, create jobs and protect natural resources all at the same time. In view of the ecological, social and economic problems caused by the overuse of natural resources and the continued increase in greenhouse gas emissions, the question of a sustainable economic order is more urgent than ever. Even the United Nations Conference on Sustainable Development, or the Rio+20 Summit for short, is dominated by the green economy debate, which is almost threatening to supplant the established concept of sustainability. Although it is emphasised that sustainable development remains the contracting parties' principal objective and that the achievement of the green economy is only a means to that end, most of the proposed measures and the debates have so far focused on strengthening environmentally compatible growth, with little attention paid to possible unintended effects on society and ecosystems. For human development and ecosystems, however, the water sector plays a key role in the implementation of many green economy projects. This paper therefore analyses the extent to which the green economy may help the water sector to achieve sustainable development and to meet the major challenges. It reaches the conclusion that, while the attention paid to the water sector that accompanies the debate on the green economy is good, the concept has serious weaknesses: On the whole, the green economy debate makes little reference to existing norms and discourses on sustainable water management. One result of this is that certain aspects of social sustainability and human development are frequently overlooked. Nor are many of the proposed measures adequately embedded in the overall ecological context, the postulated positive effects for sustainable water management thus being uncertain. Too little attention has so far been paid to conflicts of objectives between the implementation of the green economy agenda and the classical social and ecological aspects of sustainable water management. It is becoming clear that too much emphasis is being placed on the role of the private sector and too little on the responsibilities of the state as organiser of the sustainable use of natural resources. There is consequently a danger of measures / sectors in which the business community shows no interest being neglected.
Keywords: 330